Estado del arte sobre el Perfil y las Competencias del Comunicador. - Guerrero Martínez, Johana Marlene (2016)
This research focuses on the development of a state of the art , about the skills and profile Communicator , with reference to study twenty items found in the Scopus database , indexed between 2010 and 2014 , all Spanish-speaking in this way the study is based on a review of scientific production sources. This is a review of contributions that question and propose what should be the profile of the social communicator, a product of their university education. This paper aims to clarify the ideal profile of the social communicator, putting in discussion the research contributions of several authors who have conducted research works addressing the issue at hand , we believe important to the development of this work , because there are not enough contributions to cover the subject concisely, especially in Latin America . The main objective of this study is to generate a discussion on the need to clarify the output profile of the graduate student's career social communication, this need is especially apparent in demand for polyvalent professionals with extensive knowledge in other branches such as advertising, public relations, comunity manager, among others, therefore, by collecting documentation supporting concisely the view from the academy demonstrates the professional approach of social communicator.